Effect of Spheroidization Treatment on Friction Stir Processing of Al- 14 wt.% Si Alloy - Hussein, Aws Abbas (Iraqi Journal of Science, 2021)
Three different rotational speeds (800, 1000 and 1250 rpm) and traverse speeds of (0.42 mm/sec) at a constant taped pin have been employed to produce the stir zones generated from friction stir processing (FSP) of near eutectic Al- 14 wt.% Si alloy. The processed samples were thoroughly analyzed macroscopically and microscopically. The as-cast microstructure of eutectic (α Al+ Si) and primary Si were fragmented to produce spheroidization of small size of Si and deformed matrix. The stir zones showed an increase in hardness from around 45-50 Hv for as-cast to 40-65 depending on the variables applied. All the processed samples were characterized by advanced and retreated regions with large single piping defects formed mainly at the retreated region. High temperature spheroidization at 500 oC with two soaking times of 10 and 20 hrs was applied for the processed sample of 1000 rpm to investigate the effect of heat treatment on the silicon fragmentation and hardness. Growth and fragmentation of Si have taken place at soaking time of 10 hrs. At soaking time of 20 hrs noticeable microvoids and macrovoids were formed at the stir zones. Microhardness of both the advancing and the retreating regions decreased with increasing soaking time.